Naturalized bioethics: Toward responsible knowing and practice - Lindemann, Hilde (Cambridge University, 2013)
Naturalized Bioethics represents a revolutionary change in how health care ethics is practiced. It calls for bioethicists to give up their dependence on utilitarianism and other ideal moral theories and instead to move toward a self-reflexive, socially inquisitive, politically critical, and inclusive ethics.